Revaskularisation vor Defektdeckung – essenzielle Schnittstelle zwischen plastischer Chirurgie und Gefäßchirurgie - Meyer, Alexander; Rother, Ulrich; Thamm, Oliver C. (Zentralblatt für Chirurgie, 2023)
Treatment of complex ischemic lower leg defects with exposure of deep anatomic structures represents a considerable challenge to involved specialties. In selected patients, limb salvage can be achieved as an alternative to major amputation by means of a combined approach including arterial reconstruction and subsequent free flap transfer. Arterial reconstruction can be performed either by endovascular or open surgical treatment (bypass reconstruction or implantation of an arteriovenous loop) preliminary to defect reconstruction using microsurgical free flap transplantation. Whereas the aim of the arterial reconstruction comprises the establishment of sufficient perfusion and creation of adequate target vessels for the free flap transfer, the selection of the appropriate flap entity depends on the extent of the wound as wells as on the presence of osteomyelitis. Arterial reconstruction and defect reconstruction can be performed as one-stage or two-stage procedure and has become an established and feasible treatment approach in centers. Evaluation of microperfusion by means of indocyanine green can further increase safety and feasibility of this method. Against this background, combined arterial reconstruction and subsequent free flap transfer provides excellent results in terms of amputation free survival and postoperative mobility. Essential is however an individualized decision making in consideration of patient selection and possible contraindications. This approach may be evaluated in mobile patients with complex wounds prior to major amputation.
CRIS-Team Scopus Importer:2023-12-01
Keywords: bypass surgery; combined operation/surgical intervention; distal bypass surgery; endovascular; free microsurgical tissue transfer; vascular surgery